Royalties de petróleo e desenvolvimento municipal: um estudo de eficiência nos municípios do rio grande do norte - Barbosa, Kadja Kallyne Costa (Universidade Federal Rural do Semi-Árido, 2019)
The exploitation of oil generates a revenue denominated royalties, a financial compensation due by third parties to States and Municipalities. In view of this scenario, this assertion leads us to question whether the public actions offered to the population and financed with oil resources are up to the volume of royalties. Thus, this study sought to verify which municipalities in the state of Rio Grande do Norte were more efficient in the application of oil royalties revenue in the year 2016. The methodology applied in the research was descriptive, documentary and quantitative in nature. The sample covers the 15 oil-producing municipalities. As a research procedure, Data Envelopment Analysis (DEA) was used. The observed variables were the oil royalties revenue and the FIRJAN Municipal Development Index - IFDM. The results showed that only 4 (26.7%) municipalities producing oil reached the efficiency score, namely: Apodi, Areia Branca, Caraúbas and Mossoró. It is suggested that the efficiency is not related to the amount of revenue, since it was possible to perceive municipalities that have lower income were more efficient, this fact, among other possibilities can be explained by poor municipal management. This study can serve as an indicative for the evaluation of the technical efficiency of the municipal public expenditure of Potiguar, since this exercise pointed to some municipalities that can be used as a benchmark by others and thus to attract attention to a more efficient allocation of public resources aimed at improving the population
Keywords: Eficiência; Royalties; Petróleo; IFDM; Efficiency; Royalties; Oil; IFDM; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA